2004
DOI: 10.1021/om040023c
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Diaryliodine(III) Triflates toward Palladium(II) and Platinum(II):  Reactions of C(sp2)−I Bonds to Form Arylmetal(IV) Complexes; Access to Dialkyl(aryl)metal(IV), 1,4-Benzenediyl-Bridged Platinum(IV), and Triphenylplatinum(IV) Species; and Structural Studies of Platinum(IV) Complexes

Abstract: Diphenyliodine(III) triflate is able to transfer Ph + to Pd(II) and Pt(II) with cleavage of a phenyl-iodine bond and formation of metal(IV) species, leading to the first identified transfer of Ph + to Pd(II) from an aryl-halogen bond, and, for platinum, a methodology providing a facile route to dimethyl(aryl)platinum(IV) and 1,4-arenediyl-bridged Pt(IV) species and the first archetypal triarylplatinum(IV) complex. Thus, [IPh 2 ][OTf] reacts with PtMe 2 (bpy) (bpy ) 2,2′-bipyridine) at -50°C to form iodobenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 69 publications
1
58
0
Order By: Relevance
“…Arylations can be rendered catalytic because ArI is compatible with silver salts used for iodide removal from palladium coordination sphere. It has been shown that Pd(IV) complexes possessing hard ligands are isolable in some cases;8a hence, if arene contains a hard directing group and can be cyclopalladated, we should be able to arylate it. Palladacycles have been studied extensively;8b however, alternative mechanistic pathways for C-H activation by iridium complexes have also been proposed 8c…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arylations can be rendered catalytic because ArI is compatible with silver salts used for iodide removal from palladium coordination sphere. It has been shown that Pd(IV) complexes possessing hard ligands are isolable in some cases;8a hence, if arene contains a hard directing group and can be cyclopalladated, we should be able to arylate it. Palladacycles have been studied extensively;8b however, alternative mechanistic pathways for C-H activation by iridium complexes have also been proposed 8c…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, electron-rich aryl iodides react faster than electron-poor ones (Scheme 3). The aryl iodide enters the catalytic cycle at the stage of oxidative addition to Pd(II), which is most likely the rate-determining step since arylation rate depends on ArI and reductive elimination from Pd(IV) is expected to be fast 8a. Oxidative addition step must be faster for electron-rich aryl iodides which is different from the usual Pd(0)-Pd(II) coupling cycle where electron-deficient aryl halides are more reactive 15.…”
Section: Discussionmentioning
confidence: 99%
“…An analogous oxidation of cis-[Pt(C 6 F 5 ) 2 (PhN 3 Ph)] -to the corresponding dichloride has been reported [52]. Use of iodine(III) reagents to oxidize platinum / palladium(II) complexes to tetravalent derivatives is a currently active synthetic method [53][54][55][56][57][58][59]. The trans-Cl 2 arrangement in 1b was established by X-ray crystallography (below).…”
Section: Synthesis Of Pt IV Organoamidometallic Complexesmentioning
confidence: 99%
“…[13] It has been shown that diaryliodonium trifluoromethanesulfonates can transfer Ar + to nitrogen-ligated Pd II , thereby leading to the formation of unstable Pd IV species that decompose through reductive elimination pathways. [14] This finding of Canty and co-workers may be relevant to the mechanism of this arylation procedure; however, at this point a s-bond metathesis pathway can not be ruled out.…”
mentioning
confidence: 96%